2022
DOI: 10.3390/cancers14164031
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Long-Term Survival after Neoadjuvant Radiotherapy and Chemotherapy in High-Risk Breast Cancer

Abstract: Background: Neoadjuvant radiotherapy (naRT) in addition to neoadjuvant chemotherapy (naCT) has been used for locally advanced, inoperable breast cancer or to allow breast conserving surgery (BCS). Retrospective analyses suggest that naRT + naCT might result in an improvement in pathological complete response (pCR rate and disease-free survival). pCR is a surrogate parameter for improved event-free and overall survival (OS) and allows for the adaption of the post-neoadjuvant therapy regimens. However, it is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…pCR was achieved in 31.1% of patients and associated with a significant improvement in OS (HR = 0.58; 95% CI: 0.41–0.80; p = 0.001). This study not only showed that NACT and NART before surgical resection achieve good long‐term survival in high‐risk BC, but also proposed that pCR following NARCT was an independent prognostic factor for long‐term OS 57 …”
Section: Combining Preoperative Radiotherapy and Neoadjuvant Chemothe...mentioning
confidence: 77%
See 1 more Smart Citation
“…pCR was achieved in 31.1% of patients and associated with a significant improvement in OS (HR = 0.58; 95% CI: 0.41–0.80; p = 0.001). This study not only showed that NACT and NART before surgical resection achieve good long‐term survival in high‐risk BC, but also proposed that pCR following NARCT was an independent prognostic factor for long‐term OS 57 …”
Section: Combining Preoperative Radiotherapy and Neoadjuvant Chemothe...mentioning
confidence: 77%
“…This study not only showed that NACT and NART before surgical resection achieve good long-term survival in high-risk BC, but also proposed that pCR following NARCT was an independent prognostic factor for long-term OS. 57 Combining preoperative radiotherapy and chemotherapy also showed acceptable performance in terms of IBR.…”
Section: Combining Preoperative Radiotherapy and Neoadjuvant Chemothe...mentioning
confidence: 97%
“…Meanwhile, another study stated that anthracycline-based neoadjuvant chemotherapy gave better response in grade III (complete response of 24%) than tumour grade I and grade II (complete response of 0%) 20 . When viewed from the aspect of tumour differentiation, various studies have assessed the association between histological tumour grading and reported that chemotherapy response is independent of tumour grading 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The 70.8% pathological complete response (pCR) rate confirmed the effectiveness of this strategy. Additionally, a retrospective analysis of 356 patients treated with NART demonstrated a 45.1% OS after 25 years of follow-up in high-risk patients ( 46 ). Nevertheless, the patient’s age, tumor receptor stage, nodal invasion, chemotherapy type, and NART scheme are outcome-modifying factors ( 46 , 47 ).…”
Section: Basic Concepts In Breast Reconstructionmentioning
confidence: 99%